Game‐based activities targeting visual literacy skills to increase understanding of biomolecule structure and function concepts in undergraduate biochemistry. Issue 1 (28th July 2020) - Terrell, Cassidy R.; Nickodem, Kyle; Bates, Alison; Kersten, Cassandra; Mernitz, Heather
Abstract: Introductory biochemistry courses are often challenging for students because they require the integration of chemistry, biology, physics, math, and physiology knowledge and frameworks to understand and apply a large body of knowledge. This can be complicated by students' persistent misconceptions of fundamental concepts and lack of fluency with the extensive visual and symbolic literacy used in biochemistry. Card sorting tasks and game‐based activities have been used to reveal insights into how students are assimilating, organizing, and structuring disciplinary knowledge, and how they are progressing along a continuum from disciplinary novice to expert. In this study, game‐based activities and card sorting tasks were used to promote and evaluate students' understanding of fundamental structure–function relationships in biochemistry. Our results suggest that while many markers of expertise increased for both the control and intervention groups over the course of the semester, students involved in the intervention activities tended to move further towards expert‐like sorting. This indicates that intentional visual literacy game‐based activities have the ability to build underdeveloped skills in undergraduate students.